2012
DOI: 10.1002/fld.3689
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear acceleration of coupled fluid–structure transient thermal problems by Anderson mixing

Abstract: SUMMARY Conjugate heat‐transfer problems are typically solved using partitioned methods where fluid and solid subdomains are evaluated separately by dedicated solvers coupled through a common boundary. Strongly coupled schemes for transient analysis require fluid and solid problems to be solved many times each time step until convergence to a steady state. In many practical situations, a fairly simple and frequently employed fixed‐point iteration process is rather ineffective; it leads to a large number of ite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…12 and 13. The results illustrate a clear algorithmic advantage 0 1,000 2,000 3,000 4,000 5,000 6,000 7,000 8,000 0 Our current FORTRAN implementation of the method written as an interface solver between SC03 and HYDRA codes is able to reproduce the performance benefits observed in [17] on a large industrial scale model coupled to five cavities.…”
Section: Computational Performancementioning
confidence: 77%
See 1 more Smart Citation
“…12 and 13. The results illustrate a clear algorithmic advantage 0 1,000 2,000 3,000 4,000 5,000 6,000 7,000 8,000 0 Our current FORTRAN implementation of the method written as an interface solver between SC03 and HYDRA codes is able to reproduce the performance benefits observed in [17] on a large industrial scale model coupled to five cavities.…”
Section: Computational Performancementioning
confidence: 77%
“…Detailed performance analysis of the method with application to the conjugate heat transfer problems is given in [17]. The procedure starts with an initial guess of the interface temperature field T n+1 Σ,0 applied as a boundary condition to the fluid solver.…”
Section: Anderson Accelerationmentioning
confidence: 99%
“…The IQN-ILS technique [16] is an efficient [17,3] and robust black-box coupling algorithm for which convergence theorems are available in [18]. The IQN-ILS algorithm is mathematically equivalent to Anderson acceleration [19,20,21] which can be categorized as a multisecant method as discussed by Fang and Saad [22]. When applied to linear problems, it can be shown that Anderson acceleration is essentially equivalent to the GMRES method [20], which has also been shown for the IQN-ILS method [23].…”
Section: Introductionmentioning
confidence: 88%
“…if converged then mapping matrix T k does not need to be initialized with the identity matrix at line 2, but can be determined with (21). The mapping matrix T k is of size n × n which can be prohibitively large for large scale applications.…”
Section: Manifold Mapping Algorithmmentioning
confidence: 99%
See 1 more Smart Citation